Modeling Streptococcus pyogenes Pharyngeal Colonization in the Mouse - Gogos, Artemis; Federle, Michael J. (Frontiers in Cellular and Infection Microbiology, 2019)
Streptococcus pyogenes, or Group A Streptococcus (GAS), is a human-restricted pathogen most commonly found in the posterior oropharynx of the human host. The bacterium is responsible for 600 million annual cases of pharyngitis globally and has been found to asymptomatically colonize the pharynxes of 4-30% of the population. As such, many studies have utilized animals as models in order to decipher bacterial and host elements that contribute to the bacterial-pharyngeal interaction and determine differences between acute infection and asymptomatic colonization. The aim of this review is to first describe both bacterial and host factors that are important for the pharyngeal persistence of GAS in humans, then to detail the bacterial and host factors that are important for colonization in murine model, and finally to compare the two in order to evaluate the strength of murine pharyngeal colonization as a model for the human-GAS pharyngeal interaction.